Regenerative endodontics on immature permanent teeth with wide open apex: a case report - Nugroho, Juni J.; Saputra, Yennata (Journal of Case Reports in Dental Medicine, 2019)
Objective: Immature permanent teeth with open apex can be challenging in endodontic treatment along with its restoration. Several treatment options were available such as apexification, apical barrier technique and regenerative endodontics. This case report aims to describe regenerative endodontics approach in the treatment of immature permanent teeth with wide open apex (blunderbuss) in the maxillary central incisors.Methods: A 9-year-old female referred to Dental Hospital Department of Conservative with chief complaint of fractured upper central incisors due to trauma. Regenerative endodontics procedure was performed on both teeth with calcium hydroxide as intra-canal medicament.Results: The treatment was considered successful with no clinical signs or symptoms, complete apex closure and increased root wall thickness and root length as seen on follow-up radiograph.Conclusion: Regenerative endodontics is the first-choice treatment for immature teeth with pulp necrosis and produce a satisfying clinical outcomes.